Thapsigargin triggers a non-apoptotic, caspase-independent programmed cell death in basophilic leukaemia cells - Philip Steiner; Korollus Melek; Ancuela Andosch; Lena Wiesbauer; Anna Madlmayr; Michelle Duggan; Hubert H. Kerschbaum; Susanna Zierler (Cell Death Discovery)
Abstract Thapsigargin (TG), a potent inhibitor of the sarco/endoplasmic reticulum Ca²⁺-ATPase (SERCA), is widely used to study intracellular Ca²⁺ homeostasis and has shown—along prodrug derivatives—promise as an anticancer agent. While TG is traditionally considered an inducer of apoptosis, the precise mode of cell death it triggers remains incompletely defined. Here, we investigated the effects of TG on rat basophilic leukaemia (RBL-1) cells using advanced 2D and 3D transmission electron microscopy, confocal laser scanning microscopy, and functional cell death assays. TG treatment led to marked ultrastructural alterations, including pronounced ballooning of the perinuclear space, extensive vacuolization, mitochondrial enlargement and degradation, and structural anomalies of the endoplasmic reticulum. Notably, classical apoptotic features such as nuclear fragmentation, chromatin condensation and apoptotic body formation were absent. Functional assays revealed minimal caspase-3/7 activation and low Annexin V staining, indicating a caspase-independent, non-apoptotic form of programmed cell death (PCD). Morphological and quantitative analyses demonstrated that TG-induced cell death in RBL-1 cells closely resembles autosis, a non-apoptotic, autophagy-dependent PCD characterized by perinuclear space ballooning and increased autophagolysosome formation. These autosis-like features were also observed in TG-treated murine macrophages and human mast cells, suggesting a conserved mechanism across cell types. Digoxin, a Na⁺/K⁺-ATPase inhibitor, partially reversed TG-induced ultrastructural damage, supporting the involvement of Na⁺/K⁺-ATPase in this process. Ca²⁺ imaging confirmed that TG-induced cytosolic Ca²⁺ elevation is primarily driven by ER Ca²⁺ release, with extracellular Ca²⁺ amplifying the response. Our findings establish that TG induces a non-apoptotic, caspase-independent PCD matching autosis, challenging the prevailing view of TG as a classical apoptosis inducer. This insight has important implications for research on intracellular Ca2+ homeostasis as well as for the therapeutic exploitation of TG and its derivatives in targeting apoptosis-resistant cancer cells.